Fundamentals of signals and systems - Roberts, Michael J. (McGraw-Hill Higher Education, 2008)
the beauty, of physical phenomena. This is true of signals and systems. "Signals and Systems: Analysis Using Transform Methods and MATLAB" captures the mathematical beauty of signals and systems and offers a student-centered, pedagogically driven approach. The author has a clear understanding of the issues students face in learning the material and does a superior job of addressing these issues. The book is intended to cover a one-semester sequence in Signals and Systems for juniors in engineering. This text is created in modular format, so instructors can select chapters within the framework that they teach this course